HUMAN AS PHILOSOPHER AND NOTARY - Manoylo, Nataliya (Scientific Journal of Polonia University, 2023)
A person becomes a human being if he or she is capable of communication based on the disclosure of his or her inner essence, which he or she not only experiences, feels, but also expresses, writes down, and tells others about its content. The well-known saying that “someone else’s soul is twilight” captures the complexity of self-knowledge that philosophy calls for. The fact is that the essence of a person is indeed in the twilight of the bodily wrapper that hides its manifestations. Therefore, it is quite possible to argue that cognition is the process of declassifying the content that is hidden behind material bodily forms. Hence the well-known definition that consciousness is the internal state of matter. The organs of perception perceive universal forms of material existence through movement subordinated to internal forces, which, by revealing and projecting outward not only aloud but also through writing, can reveal information about them and their inherent energy potential. M. Mamardashvili defined philosophy as consciousness out loud, but it is always desirable not only to voice any reflections on the “last and ultimate” foundations of existence, as Heidegger defined its essence, but also to write them down, thereby preserving them for posterity, as well as for contemporaries, who thus have the opportunity to join the discussion and, thus, to some extent, to solve problems that concern people but which must be constantly addressed by each new generation.